(untitled) (Journal of Information Technologies in Education (ITE), 2011)
Purpose of the article is to point how to organize the work of students at creation of «complex project» at the study of educational material of Informatics during a whole year in school. The educational project provides the practical research approach to search of creative decisions for the urgent needs of the real life. Pupils step by step acquire not only educational material but also find the ways of the practical use of computer information technologies.